SOCIALIZATION OF YOUTH IN MODERN SOCIETY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article refers the reasoning about personality and its socialization, to focus on the factors that can make this process effective. Meanwhile, socialization presupposes a high degree of inner activity of the individual, the need for its self-realization. In other words, a lot depends on the person, his ability to manage his own activities.